Development of 3D-printed composite adsorbents for carbon dioxide capture from waste recovery - Correia, Inês do Carmo Pedro (2023)
This Master’s thesis focuses on the development of a 3D-printed composite adsorbent for capturing carbon dioxide (CO₂), a greenhouse gas contributing to global climate change. The research investigates the synergistic potential between biochar derived from chitosan and porous inorganic polymers incorporating red mud, a waste product of alumina production, to create a composite material with tailored textural properties using additive manufacturing techniques. Biochar, a carbonaceous material derived from the pyrolysis of waste materials and biomass, has shown promise as a CO₂ adsorbent due to its carbon sequestration properties and sustainable sourcing. In this study, the impact of different heating methods and pyrolysis temperatures on the characteristics and adsorption behavior of chitosan-derived biochar is investigated. The findings contribute to the understanding of biochar properties and the optimization of its performance as a CO₂ adsorbent. The biochar with superior CO₂ adsorption capacity was subsequently immobilized, obtaining a biochar/inorganic polymer composite in order to minimize the limitations associated with the use of adsorbents in powder form. An additional innovative aspect of this project is the utilization of additive manufacturing techniques that aims to fabricate the composite adsorbent with controlled pore morphology and increased open porosity. Finally, the synergistic effect of the immobilised biochar on the 3D-printed geopolymer was evaluated by determining the adsorption capacity and selectivity. The outcomes of this thesis contribute to the development of sustainable CO₂ capture technologies and offer novel approaches for effective carbon dioxide mitigation.